Re-imagining Japan after Fukushima - Mihic, Tamaki (Asian studies series monograph, 2020)
"The Tōhoku earthquake and tsunami that hit Japan on 11 March 2011 (3.11) was an event of unforeseen proportions. A magnitude 9.0 earthquake was followed by 9.3-metre-high tsunami waves over the coast of northeastern Japan, which claimed the lives of nearly 20,000 people and obliterated communities. The earthquake began at 2.46 pm, which meant that most children were at school and were guided to higher ground in anticipation of a tsunami. Over 240 children were orphaned as a result. Numerous medical and administrative institutions were destroyed when they were most needed and 160,000 people were forced to move to temporary shelters.1 However, the disaster did not end there nearly 700 aftershocks of magnitude 5 or greater were recorded within a year of 3.11 (Ministry of Economy, Trade and Industry, 2012). Further, 3.11 developed into a triple disaster, with the subsequent meltdown of three nuclear reactors at the Fukushima Daiichi power plant, which caused 344,000 people to evacuate from the affected areas (Reconstruction Agency, 2012). Many continue to suffer, especially from the effects of the nuclear disaster, while the rest of the nation attempts to move on. There is no doubt that 3.11 has left a permanent scar on the lives of many even if they did not lose their friends and loved ones, they lost their livelihood, their homes and their lifestyles." --page 1.